Instability of cyclic superelastic deformation of NiTi investigated by synchrotron X-ray diffraction. (1st August 2015) - Sedmák, P.; Šittner, P.; Pilch, J.; Curfs, C.
Abstract: Motivated by an assumption that the instability of the cyclic tensile superelastic behavior of NiTi polycrystal is linked to its fatigue performance (number of cycles till failure), the instability was investigated by high resolution in situ synchrotron X-ray diffraction method. NiTi wires were cyclically deformed in tension at room temperature while X-ray diffraction patterns were recorded in three preselected states along the superelastic stress–strain curve, analyzed and interpreted in terms of the gradual evolution of microstructural state during cycling. It is found that the cyclic instability is due to the gradual redistribution of internal stresses originating from the accumulation of incremental plastic strains accompanying the stress induced martensitic transformation in constrained polycrystalline environment. The degree of cyclic instability increases with the increasing involvement of slip in the hybrid slip/transformation process, which depends on initial microstructure (grain size, defects, precipitates), martensitic transformation (crystallographic incompatibility between transforming phases), temperature and parameters of the cyclic loading (strain rate, amplitude, stress state, type of loading etc.).